PENGARUH RAGAM KONSELI SUKARELA DAN PERILAKU NONVERBAL KONSELOR TERHADAP KEBERHASILAN PROSES - Wandana, Etya (Educatio Vitae, 2014)
In the context of counseling, the voluntary counselee (based on selfunderstanding and motivation) will support the achievement of the counseling process. Besides voluntary counselee variety, communication skills used by a counselor, especially nonverbal behavior are also needed in the counseling process. Thus, the voluntary counselee is close to the counselor and the use of nonverbal communication skills of counselors determines the achievement of the counseling process. Furthermore, this research aims to analyze the effect of voluntary counselee variety and counselor nonverbal behavior toward counseling process. The population in this research were all students of SMAK St. Bonaventura Madiun in the school year 2013/2014 who had received counseling services during February 2013-October 2013 by 100 students, the sampling techniques used by the researcher is Saturated Sampling. Data which were obtained by using the questionnaire method is voluntary counselee variety scale, nonverbal behavior of counselor scale, and the success of the counseling process scale.   There were three hypotheses as the proposes of the research: 1) Voluntary counselee variety affect the achievement of the counseling process, 2) Nonverbal behavior of counselor affect the achievement of the counseling process, 3) Voluntary counselee variety and nonverbal behavior of counselor affect the achievement of the counseling process.   The analysis technique used was multiple linear regression techniques. The research proved that there was the influence of verbal counseling techniques toward the achievement of counseling process. There was an internal condition which influenced the achievement of counseling process. There was the influence of verbal counseling techniques and internal condition toward the achievement counseling process. R = 0.528, the effective contribution of 0,279%, means that 27.9% the achievement of counseling process was influenced by voluntary counselee variety and nonverbal behavior of counselor, while the remaining 72.1% was influenced by other variables which was not analyzed in this research.